Thoracic dorsal root ganglion stimulation reduces acute myocardial ischemia induced ventricular arrhythmias - Kuwabara, Yuki; Howard-Quijano, Kimberly; Salavatian, Siamak; Yamaguchi, Tomoki; Saba, Samir; Mahajan, Aman (Frontiers in Neuroscience, 2023)
BACKGROUND: Dorsal root ganglion stimulation (DRGS) may serve as a novel neuromodulation strategy to reduce ischemia-induced cardiac sympathoexcitation and ventricular arrhythmias. OBJECTIVE: This pre-clinical study investigated the effectiveness of DRGS on reducing ventricular arrhythmias and modulating cardiac autonomic imbalances caused by myocardial ischemia. METHODS: Twenty-three Yorkshire pigs were randomized to LAD or LAD+DRGS groups. In the DRGS group (n =10), high-frequency stimulation (1 kHz) at the second thoracic level (T2) was initiated 30 minutes before ischemia and continued throughout one hour of ischemia and two hours of reperfusion. Cardiac electrophysiological mapping and Ventricular Arrhythmia Score (VAS) were assessed, along with evaluation of cFos expression and apoptosis in the T2 spinal cord and DRG. RESULTS: DRGS decreased the magnitude of activation recovery interval (ARI) shortening in the ischemic region (LAD: -201  9.8 ms. DRGS: -170  9.4 ms, p = 0.0373) and decreased global dispersion of repolarization (DOR) at 30 minutes of myocardial ischemia (LAD: 9546  763 ms2. DRGS: 6491  636 ms2, p = 0.0076). DRGS also decreased ventricular arrhythmias (VAS - LAD: 8.9  1.1. DRGS: 6.3  1.0, p = 0.038). Immunohistochemistry studies showed that DRGS decreased % cFos with NeuN expression in the T2 spinal cord (p = 0.048) and the number of apoptotic cells in the DRG (p = 0.0084). CONCLUSION: DRGS reduced the burden of myocardial ischemia-induced cardiac sympathoexcitation and has a potential to be a novel treatment option to reduce arrhythmogenesis.